The English School in Transition: Dialogues, Adaptations, and Limitations - Mürsel Doğrul (Güvenlik Stratejileri Dergisi)
This article examines the contributions of the English School to the development of Global International Relations (Global IR) through a critical analysis of its systemic framework, historical development, and normative theoretical focus. By undertaking a qualitative and historical analysis of foundational texts by figures such as Manning, Wight, and Bull, as well as relevant secondary literature, the study illuminates the interaction between the English School and Global IR. The study's key findings indicate that, while the English School's Eurocentric legacy presents theoretical constraints, its focus on norms, international society, and justice offers valuable frameworks for addressing contemporary global challenges. Furthermore, the study identifies the integration of emerging powers and non-Western perspectives as evidence of the English School's adaptability in a pluralistic global order. Methodologically, the study's focus on historical analysis and qualitative approaches constrains its capacity to offer broader empirical generalisations. Additionally, its theoretical scope reflects the challenges of reconciling diverse perspectives within a cohesive framework. Despite these limitations, the article highlights the potential for transformative dialogue between the English School and Global IR, with practical implications for fostering inclusive global governance and providing pathways for future interdisciplinary research.